Worker Churn and Employment Growth at the Establishment Level - Rüdiger Bachmann; Christian Bayer; Christian Merkl; Stefan Seth; Heiko Stüber; Felix Wellschmied (Institute of Labor Economics (IZA), 2017)
We study the relationship between employment growth and worker flows in excess of job flows (churn) at the establishment level using the new German AWFP dataset spanning from 1975–2014. Churn is above 5 percent of employment along the entire employment growth distribution and most pronounced at rapidly-adjusting establishments. We find that the patterns of churn along the employment growth distribution can be explained by separation rate shocks and time-to-hire frictions. These shocks become larger on average during boom periods leading to procyclical worker churn. Distinguishing between separations into non-employment and to other establishments, we find that separations to other establishments drive all procyclical churn. In a secondary contribution, we compare German worker and job flows with their US counterparts and recent US findings.
Keywords: E20; E24; E32; J23; J63; 330; job flows; worker flows; churn; job-to-job transitions; aggregate fluctuations